Long Cold Ischemia Times in Same Hospital Deceased Donor Transplants. Issue 3 (March 2018) - Chow, Eric K.; DiBrito, Sandra; Luo, Xun; Wickliffe, Corey E.; Massie, Allan B.; Locke, Jayme E.; Gentry, Sommer E.; Garonzik-Wang, Jacqueline; Segev, Dorry L.
Abstract : Background: Recent changes in deceased donor organ allocation for livers (Share-35) and kidneys (kidney allocation system) have resulted in broader sharing of organs and increased cold ischemia time (CIT). Broader organ sharing however is not the only cause of increased CIT. Methods: This was a retrospective registry study of CIT in same-hospital liver transplants (SHLT, n = 4347) and same-hospital kidney transplants (SHKT, n = 9707) between 2004 and 2014. Results: In SHLT, median (interquartile range) CIT was 5.0 (3.5-6.5) hours versus 6.6 (5.1-8.4) hours in other-hospital LT. donation after circulatory death donors, donor biopsy, male recipient, recipient obesity, and previous transplant were associated with increased CIT. Model for End-Stage Liver Disease at transplant of 29+ or status 1a was associated with decreased CIT. SHLT CIT varied by Organ Procurement Organization and transplant-center ( P < 0.01), with center median CIT ranging from 2.0 to 7.8 hours across 118 centers. In SHKT, CIT was 13.0 (8.5-19.0) hours versus 16.5 (11.3-22.6) hours in other-hospital KT. Overweight donors, donation after cardiac death donors, right-kidney, donor biopsy, recipient obesity, use of mechanical perfusion, additional KT procedures on the same day, and transplant center annual volume were associated with increased CIT. Older donor age, extended criteria donors, and underweight recipients were associated with decreased CIT. SHKT CIT varied by Organ Procurement Organization and transplant-center ( P < 0.001), with center median CIT ranging from 3.3 to 29 hours across 206 centers. Transplant centers with longer SHKT also had longer SHLT ( P = 0.01). Conclusions: Same-hospital transplants already have a significant amount of CIT, even without transporting the organ to another hospital. Abstract : In this retrospective registry data analysis, the authors study the influence of local factors on cold ischemia time in both livers and kidney transplantation with a comparison with nonlocal same organ transplants.